Desensitization protocol to lenalidomide: An effective and safe treatment modality for delayed hypersensitivity‐induced rash in patients with multiple myeloma. (2nd January 2023) - Shamriz, Oded; Parnasa, Elchanan; Rubin, Limor; Talmon, Aviv; Ribak, Yaarit; Lebel, Eyal; Vainstein, Vladimir; Aumann, Shlomzion; Saban, Revital; Gatt, Moshe E.; Tal, Yuval
Abstract: Introduction and Objectives: Lenalidomide is considered a standard of care in multiple myeloma (MM) Some MM patients will develop delayed hypersensitivity to lenalidomide, which can lead to treatment discontinuation. Desensitization to lenalidomide can help these patients to complete treatment courses. Here, we aimed to review lenalidomide‐treated MM patients who developed delayed hypersensitivity‐induced rash and were treated with desensitization. Methods: A retrospective analysis of medical files of MM patients, who were desensitized to lenalidomide due to delayed hypersensitivity rash. Patients were treated between 2018 and 2022 at Hadassah Medical Center, Jerusalem, Israel. Results: Search of patients yielded 16 patients that underwent desensitization to lenalidomide within the study period. The desensitization protocol consisted of a slow, 3‐week‐long protocol with lenalidomide's target doses of 10, 15, and 25 mg/day. Of the 16 patients, 10 (62.5%) succeeded to complete the protocol and thus were able to complete lenalidomide treatment cycles. One patient with unsuccessful desensitization was subsequently treated with first‐generation IMiD thalidomide, with no rash appearing. None of the patients that were treated with desensitization had severe immune‐mediated or non‐dermatological adverse reactions. Conclusions: Desensitization to lenalidomide is safe and effective. Discontinuation of lenalidomide in MM patients with delayed hypersensitivity and no contraindication to desensitization should be discouraged. Collaboration between hematologists and allergists is needed.